Les projets de paix perpétuelle : une "utopie" fédéraliste au siècle des Lumières - Marc Belissa (Centre de Recherches sur les Mondes Américains, 2008)
Enlightmenment philosophers’ thoughts on, and commitment to peace was multi-faceted and closely linked to the notion of federalism. A federation was conceived of as a republican alliance against usurpers and conquerors, but also as defensive association among states -- it was even regarded as an effective community among peoples. What kind of a federation did thinkers ranging from the Abbé de Saint-Pierre to Kant have in mind? An association of princes and sovereigns, or of republican peoples? Does the very form assumed by a federation guarantee peace among peoples?